Effect Of Operating Leverage On The Market Value Of Common Shares: An Applied Study - Iftikhar Jabbar Abed; Majid Fahem Jaafar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research aims to know the impact of operating leverage on the market value of ordinary shares of industrial sector companies listed on the Iraqi Stock Exchange for the period (2011-2020), based on the data obtained and published in the reports and financial statements of the relevant companies, and after descriptive and deductive analysis. To test its data and hypotheses, the research reached many results, including: There is an effect of operating leverage on the market value of shares in industrial companies (Al-Mansour Pharmaceutical Industries, Baghdad Soft Drinks, Al-Kindi for the Production of Vaccines and Veterinary Medicines, Al-Erqia Carpets and Furnishings Company, Chemical and Plastic Industries), and the results reached the following: There is an effect of operating leverage on the market value of common shares in the companies studied.